Conserved regulatory core and lineage-specific diversification of light–temperature integration in plants - Bruno Catarino; Fernando Rodríguez-Marín; Cristina Úrbez; Christina Arvanitidou; Eva Álvarez; Federico Valverde; José Manuel Franco-Zorrilla; Francisco Romero-Campero; Miguel A. Blázquez (Proceedings of the National Academy of Sciences, 2026)
Plants rely on environmental information such as light and temperature to control growth and development. Integrating these cues improves developmental precision, yet it remains unclear how this capacity is distributed across major plant lineages and how it diversified during evolution. We investigated light–temperature integration across major green plant lineages with particular attention to the origin and early diversification of land plants. Using comparative phenotypic and transcriptomic analyses, we examined responses to combined light and temperature signals in a chlorophyte alga, a streptophyte alga, a bryophyte, and a flowering plant. Streptophytes showed synergistic developmental and transcriptional responses, whereas the chlorophyte representative displayed predominantly additive behavior, indicating that the streptophyte lineage underwent a significant elaboration in environmental signal integration. Functional genetic analyses revealed that phytochromes and the transcription factors PHYTOCHROME INTERACTING FACTOR and ELONGATED HYPOCOTYL 5 are conserved regulators of this integration in land plants. Cistromic analyses further showed that diversification of downstream transcriptional responses is associated with lineage-specific redistribution of conserved cis -regulatory elements. Together, these results support the view that the capacity for light–temperature integration was established early during streptophyte evolution and diversified through lineage-specific changes in gene regulatory landscapes.